Pengaruh Loan to Deposit Ratio (LDR) dan Non Performing Loan (NPL) Terhadap Profitabilitas pada Bank Perkreditan Rakyat (BPR) di Kabupaten Sidoarjo, Jawa Timur Tahun 2019-2021 - Hari Yunan Prihatinto; Pompong B Setiadi (Cakrawala Repositori IMWI, 2023)
This study aims to determine the effect of non-performing loan (NPL) and Loan to Deposit Ratio (LDR) variables on the profitability of Rural Banks in Sidoarjo Regency as proxied by Return On Assets (ROA) for the 2019-2021 period. The sampling technique uses purposive sampling method with certain criteria, namely Rural Banks (BPR) that have been registered with the Financial Services Authority (OJK). The type of data used is secondary data, namely data on the publication reports of Conventional BPRs on the ojk.go.id website. 2019-2021 period. This research data analysis technique uses multiple linear regression analysis. The samples used in this study amounted to 30 Rural Banks (BPR) registered with the Financial Services Authority (OJK). The results showed that Non Performing Loan (NPL) has a negative effect on profitability and Loan to Deposit Ratio (LDR) has a positive effect on profitability.